Effects of different doses of levosimendan combined with Shenmai injection on immune function and galectin-3 and HSP70 levels in rats with acute heart failure. Issue 1 (1st January 2021) - Xu, Jie; Song, Zhenhua; Li, Lianfang; Liu, Wei; Zhang, Mingming; Li, Jian
Abstract : To investigate the effects of different doses of levosimendan combined with Shenmai injection on immune function and galectin-3 and heat shock protein 70 (HSP70) levels in rats with acute heart failure. Forty eight specific-pathogen free Sprague Dawley male rats were selected and divided into 6 groups according to different administration schemes after the heart failure model was established. The left ventricular end diastolic diameter (LVEDD) and left ventricular ejection fraction (LVEF) of rats in each group were observed before and after treatment. After treatment, rats in groups A–D and the model group (MG) showed decreased LVEDDs compared with the control group (CG), and group D showed the highest reduction. In contrast, rats in groups A–D and the MG showed increased LVEFs compared with the CG, and group D showed the highest increase. The MG and groups A–D rats showed an increased percent of CD3+ T cells and CD4+/CD8+ T cell ratio compared with the CG. Levosimendan combined with Shenmai injection optimized the maintenance of immune and cardiac function in rats with acute heart failure compared with Shenmai injection alone. The higher dose of levosimendan combined with Shenmai injection improved the inflammatory reaction and levels of galectin-3 and HSP70.